Pengaruh Mirror Therapy terhadap Kemandirian Aktivitas Berpakaian pada Pasien Stroke di RSUP Dr. Tadjuddin Chalid Makassar - Nunik Wahyuningsih; Rina Kurnia (Politeknik Kesehatan Kemenkes Surakarta, 2023)
Abstract Background. Stroke can cause paralysis on one side of the body, thus hampering daily activities, one of which is dressing. Mirror therapy is a form of exercise in the form of motor visual illusions that function to improve functional abilities through mirror media. This study aims to determine the effect of mirror therapy on the level of independence in dressing activities in stroke patients. Research Methodology. This type or research is quantitative with a one group pretest - posttest design. the sample collection technique used purposive with a sample of 32 people. Dressing examination using Nottingham Stroke Dressing Assessment (NSDA) instrument. The intervention was carried out with a duration of 20 minutes, 5 times a week for 4 weeks. The data analysis technique used paired sample t- test with SPSS version 25.0 program. The Result of the Research. Based of the characteristics of the respondents, 10 (31,3%) occurred in the elderly, 12 (37,5%) males, 20 (62,5%) females, 20 (62,5%) stroke onset 1-4 months, there were increased ability to dress after the intervention (mean = 68,96) compares to before the intervention (mean = 63,53). The result of the paired sample t-test statistic showed that the value was 0,001 where the value was <0,05. Conclusion. Mirror therapy has an effect on the level of independence in dressing activities for stroke patients at RSUP Dr. Tadjuddin Chalid Makassar. Reference: 45 (1983-2016) Keyword: mirror therapy, dressing activities, stroke